Melhorias na rede de uma companhia de desenvolvimento da região metropolitana de Belém - LOBATO, Natã Ferreira (2023)
Controlled cabling together with network segmentation and asset monitoring techniques seek to improve the performance of activities that are carried out through the computer network. In a Development Company in the Metropolitan Region of Belém (CODAB), many problems were found when carrying out day-to-day tasks common to the network environment. The project was based on Brazilian technical norms, allowing a reorganization and standardization of the existing cabling, together with the implementation of techniques that allow the segmentation and monitoring of the network. At the end of the project implementations, an organized, standardized network was obtained, with all its connections identified, segmented by sector and monitored at various points. Improvements were made to the network that helped in advanced routines and enabled optimization and more security to the network.